Comparison of knee and hip kinematics during landing and cutting between elite male football and futsal players - Daneshjoo, A.; Nobari, H.; Kalantari, A.; Amiri-Khorasani, M.; Abbasi, H.; Rodal, M.; Pérez-Gómez, J.; Ardigò, L. P. (healthcare, 2021)
To design an accurate sport injury prevention program, alterations in the knee and hip kinematic variables involved in injury mechanisms should be known. The main purpose of the current study was to compare knee and hip kinematic variables during landing and cutting among male football and futsal players, and to discuss them within an injury description frame. Twenty football (20.5 ± 2.1 years., 74.5 ± 6.9 kg and 1.79 ± 0.07 m) and twenty futsal players (20.3 ± 2.0 years., 73.5 ± 7.1 kg and 1.78 ± 0.07 m), with at least three years` experience of playing in the Kerman Province League, participated in this study. Hip flexion, knee flexion and knee valgus angle during two main movements with risk of injury, such as landing and cutting, were measured using a motion capture system with passive markers at 120-Hz sampling frequency. Landing and cutting maneuvers were administered in as natural way as possible. Results showed significant differences in landing and cutting maneuvers between groups in hip flexion, knee flexion and knee valgus angle. Results indicated that footballers have less extension of hip and knee joints than futsal players in landing maneuvers, which may be due to the higher requirement of jumping-landing maneuvers when playing football. In cutting maneuvers, footballers showed less hip and knee flexion than futsal players, whereas the knee valgus angle in cutting maneuvers was lower in futsal players. More information on the injury mechanisms of landing and cutting in football and futsal are needed to improve the design of injury prevention programs.